Las especies argentinas de Notholaena - Weatherby, Charles Alfred (Lilloa, 2021)
The author carries out a taxonomic study giving a key and descriptions of the six species of the genus Notholaena that inhabit Argentina: N. sinuata (Lag.) Kaulf., N. aurea (Poir.) Desv., N. buchtieniti Rosenst., N. obducta (Mett. ex Kuhn) Baker, N. squamosa (Gill. ex Hook. et Gray.) Lowe, and N. arequipensis (Maxon) and describes a new species from Paraguay: N. Hassleri.